Prevalence and Severity of Anemia in Women Attending Gynecology Clinics for Abnormal Uterine Bleeding: A Cross-Sectional Evaluation - Munawar Afzal, Shumaila Riaz, Naila Rafique, Nimra Bisharat, Sajida Imran, Hooria Rasheed, Afshan Arshad, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Abnormal uterine bleeding (AUB) is a frequent gynecological complaint that significantly affects women’s health, often leading to anemia. Anemia, particularly iron deficiency anemia, is a common complication of chronic blood loss and can impair physical, cognitive, and reproductive health. Despite its importance, limited data are available from Pakistan on the burden of anemia in women with AUB. Aims and Objectives: This study aimed to determine the prevalence and severity of anemia among women presenting with AUB and to assess its association with demographic and clinical factors. Methodology: A cross-sectional study was conducted over one year, from August 2022 to August 2023, at THQ Hospital Khairpur, District Bahawalpur, and DHQ Teaching Hospital Narowal. One hundred women aged 18–50 years with AUB were enrolled. Demographic and clinical data were collected, and hemoglobin levels were measured using automated hematology analyzers. Anemia was classified according to World Health Organization (WHO) criteria as mild, moderate, or severe. Data were analyzed using SPSS version 25. Results: The prevalence of anemia was 64%, with moderate anemia being most common (42%), followed by mild (18%) and severe anemia (4%). Menorrhagia was the leading cause of AUB and was associated with the highest anemia prevalence (78%), followed by metrorrhagia (66%), polymenorrhea (50%), and oligomenorrhea (33%). Multiparity and low socioeconomic status were significant risk factors (p < 0.05). Conclusion: Anemia is highly prevalent among women with AUB, particularly in those with menorrhagia, high parity, and low income. Routine screening and integrated anemia management are critical to improving women’s health outcomes. Keywords: Abnormal uterine bleeding, anemia, menorrhagia, prevalence, multiparity, Pakistan